Exploring the Implementation of Reading to Learn Strategy for Teaching Reading Comprehension to EFL Learners: A Case Study - Hadi, Abdul; Ramadhani, Sari (Indonesian Journal of Integrated English Language Teaching, 2024)
This study aims to explore the implementation of the Reading to Learn (R2L) strategy in teaching reading comprehension to English as a Foreign Language (EFL) learners at a vocational high school in Riau. By utilizing the six stages of the R2L strategy, the research systematically delves into how this method was applied to enhance reading comprehension among EFL learners through a thorough and in-depth qualitative approach. The study employed a qualitative case study research design, selecting an English teacher and three EFL learners as participants using a purposive sampling technique. Data were gathered through interviews and observations, and the subsequent analysis revealed that the implementation of the R2L strategy was less than satisfactory. Furthermore, the study found significant variability in participants' responses regarding the execution of each stage of the R2L strategy. This inconsistency underscores the need for improvements in the implementation process to fully capitalize on the potential benefits of the R2L strategy for teaching reading comprehension to young and adolescent EFL learners. The findings suggest that refining the application of the R2L strategy could lead to more effective teaching outcomes and better reading comprehension skills among EFL learners.